Use of Associated Chromatographic Techniques in Bio-Monitored Isolation of Bioactive Monoterpenoid Indole Alkaloids from Aspidosperma ramiflorum - Chierrito, Talita Perez Cantuaria; Cunha, Ananda de Castro; Koike, Luzia; Gonçalves, Regina Aparecida Correia; Oliveira, Arildo José Braz de (IntechOpen, 2012)
None